2022
DOI: 10.3389/fbioe.2022.958669
|View full text |Cite
|
Sign up to set email alerts
|

Methods and criteria for validating the multimodal functions of perinatal derivatives when used in oncological and antimicrobial applications

Abstract: Perinatal derivatives or PnDs refer to tissues, cells and secretomes from perinatal, or birth-associated tissues. In the past 2 decades PnDs have been highly investigated for their multimodal mechanisms of action that have been exploited in various disease settings, including in different cancers and infections. Indeed, there is growing evidence that PnDs possess anticancer and antimicrobial activities, but an urgent issue that needs to be addressed is the reproducible evaluation of efficacy, both in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…The data of the PnD e-questionnaire show that the respondents had different priorities in this regard. However, our SPRINT COST Action has recently published a quadrinomial series of consensus reviews to improve the quality of in vitro testing linked to i) inflammation, angiogenesis and wound healing ( Flores et al, 2022 ), ii) oncological and antimicrobial applications ( Silini et al, 2022 ), iii) immunomodulatory functions ( Papait et al, 2022 ), and (iiii) PnD applications in brain, bone, skeletal muscle, heart, intestinal, liver, and lung pathologies ( Pozzobon et al, 2022 ). These publications not only provide researchers with guidance on which tests are appropriate, but also discuss advantages and disadvantages of assessing functionality.…”
Section: Current Obstacles and Future Recommendations For Pnd ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The data of the PnD e-questionnaire show that the respondents had different priorities in this regard. However, our SPRINT COST Action has recently published a quadrinomial series of consensus reviews to improve the quality of in vitro testing linked to i) inflammation, angiogenesis and wound healing ( Flores et al, 2022 ), ii) oncological and antimicrobial applications ( Silini et al, 2022 ), iii) immunomodulatory functions ( Papait et al, 2022 ), and (iiii) PnD applications in brain, bone, skeletal muscle, heart, intestinal, liver, and lung pathologies ( Pozzobon et al, 2022 ). These publications not only provide researchers with guidance on which tests are appropriate, but also discuss advantages and disadvantages of assessing functionality.…”
Section: Current Obstacles and Future Recommendations For Pnd ...mentioning
confidence: 99%
“…Our SPRINT COST Action has recently published a series of consensus reviews on the relevance and potency of classical and new in vitro assays to demonstrate efficacy and potential MoA of PnD ( Flores et al, 2022 ; Papait et al, 2022 ; Pozzobon et al, 2022 ; Silini et al, 2022 ). Given the strong representation of PnD experts in the SPRINT COST Action, we now seek to address the issue of PnD definition and their characterization and provide a checklist of criteria that should be considered for any future study regarding PnD isolation, characterization and in vitro testing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to extracellular macromolecules, such as collagens, laminins, proteoglycans and hyaluronic acid, hAM is a source of stem cells and various active signalling molecules, including interleukin 6 (IL-6), tumour necrosis factor alpha (TNF-α), transforming growth factor beta (TGF-β), epidermal growth factor (EGF), interferon gamma (IFN-γ) and tissue inhibitor of metalloproteinases 1–4 (TIMP1-4) 13 – 15 . In recent years, a growing body of research has shown that the hAM has anticancer potential 16 – 21 . Namely, it has been shown that hAM preparations, hAEC and hAMSC as well as hAM scaffolds, inhibit the proliferation of muscle-invasive bladder cancer urothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are increasingly being used in clinical trials, e.g., for chronic graft-versus-host disease following haematopoietic stem cell transplantation [2]. Although the precise mechanism of action (MOA) of these cells in various clinical applications is not fully understood, recent progress has been made in the functional characterisation of MSCs and their extracellular vesicles, especially in the perinatal field [3][4][5][6], which can easily been translated to adult MSCs.…”
mentioning
confidence: 99%